Biomimetic polymersomal nanoreactors for hepatocyte-directed detoxification in drug-induced liver injury - Wenxing Gu; Ruxue Bai; Jiaxin Wang; Jun Wang; Chongzhou Fang; Yuanchao Shi; Peixing Wang; Qiaoqiao Wang; Wei Bing; Tian Xie; Jing Mu (Materials Today Bio)
Drug-induced liver injury (DILI) is a major clinical concern associated with drug toxicity, primarily characterized by hepatocyte damage driven by oxidative stress and inflammation. Excessive accumulation of reactive oxygen species (ROS) and pro-inflammatory cytokines exacerbates liver injury, necessitating effective therapeutic interventions. While natural antioxidant enzymes exhibit high catalytic activity and specificity in ROS scavenging, their clinical use is limited by poor stability in circulation and limited cellular uptake. To address these challenges, we developed antioxidant polymersomal nanoreactors (CS@PS) for the targeted co-delivery of catalase (CAT) and superoxide dismutase (SOD). CS@PS functions as a cascade system, efficiently neutralizing ROS and mitigating inflammation in hepatocytes. Notably, systemic administration of CS@PS exhibits targeted delivery to hepatocytes, ensuring enzyme stability and bioavailability. In a model of acetaminophen-induced liver injury, CS@PS significantly reduced hepatic ROS levels and alleviated liver damage, underscoring its therapeutic potential. This study highlights the promise of CS@PS as an innovative antioxidant nanoreactor for DILI treatment offer a promising strategy for managing other ROS-mediated diseases.